Gut microbiota therapy for chronic kidney disease - Liu, Chunguang; Wang, Junhong; Lei, Lei; Li, Liping; Yuan, Xingxing (Frontiers in Immunology, 2025)
Chronic kidney disease (CKD), affecting 13% of the global population, is increasingly linked to gut microbiota dysbiosis, a condition driven by uremic toxins accumulation, metabolic alterations, and dietary factors. This mini review explores gut microbiota modulation as a therapeutic strategy to alleviate CKD symptoms, focusing on interventions that target gut microbiota composition and function. Prebiotics, such as resistant starch, have been shown to lower uremic toxins and reduce inflammation, while dietary adjustments, including low-protein and gluten-free diets, modulate microbial diversity and improve renal biomarkers. Fecal microbiota transplantation (FMT), which stabilizes creatinine levels and shifts gut microbiota toward beneficial taxa, represents another promising approach. However, limitations persist: synbiotics, which often induce gut microbiota shifts, frequently lack clinical impact; probiotics, which enhance glucose control and oxidative stress mitigation, exhibit variable efficacy; and interventions such as propolis or cranberry extract, which have been tested, prove ineffective. The causal relationship between gut microbiota dysbiosis and CKD progression, which remains unclear, is further complicated by methodological heterogeneity across studies. Emerging strategies, including phage therapy and artificial intelligence-driven multi-omics integration, which hold significant promise, require further validation. Future research must prioritize longitudinal studies, maternal gut microbiota optimization, and personalized approaches, which are essential for advancing CKD management. While gut microbiota modulations hold therapeutic potential, translating these findings into clinical practice demands rigorous trials to address inconsistencies and establish mechanistic links, ultimately shifting CKD management from reactive treatment to precision-based prevention.